Core concepts in fashion - Dias, Laura Portolese (McGraw Hill, 2008)
This book offers a hands-on, fun approach to learning fashion. The content and the style of the book is organized to discuss the three major areas of fashion. The supplemental material is full of projects and in class activities-especially useful for the longer, blocked course. This book is full of pictures and charts for our visual learners.